2018
DOI: 10.1002/ccd.24888
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Transfemoral Transcatheter Aortic Valve Replacement with a Balloon‐Expandable Prosthesis: The Importance of Preventative Measures and Contingency Planning

Abstract: Transcatheter aortic valve replacement (TAVR) with balloon-expandable Edwards-SAPIEN valve was superior to standard therapy in inoperable patients and noninferior to surgical aortic valve replacement in high surgical-risk, but operable patients, with severe symptomatic aortic stenosis in the randomized controlled PARTNER trial. Since the first case of TAVR with a balloon-expandable valve in 2002, several groups have reported their experience with balloon-expandable valves with high-procedural success. In the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…TAVI, by itself, is associated with significant complications that include vascular problems, valve malpositioning, regurgitation, embolization, coronary compromise, conduction abnormalities, stroke, transient ischemic attack, acute kidney injury, cardiac tamponade, and hemodynamic collapse. 15 Early identification by thoroughly looking out for these complications and timely intervention is important for successful outcomes. The systematic review by Chakos and colleagues 16 looking at long-term outcomes of TAV1 in nearly 14 000 patients from a worldwide registry showed that survival post-TAVI is significantly inferior when compared against an age-matched population, but this is not unexpected, given the significant comorbidities in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…TAVI, by itself, is associated with significant complications that include vascular problems, valve malpositioning, regurgitation, embolization, coronary compromise, conduction abnormalities, stroke, transient ischemic attack, acute kidney injury, cardiac tamponade, and hemodynamic collapse. 15 Early identification by thoroughly looking out for these complications and timely intervention is important for successful outcomes. The systematic review by Chakos and colleagues 16 looking at long-term outcomes of TAV1 in nearly 14 000 patients from a worldwide registry showed that survival post-TAVI is significantly inferior when compared against an age-matched population, but this is not unexpected, given the significant comorbidities in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization into the aorta can sometimes be treated by valve repositioning and deploying into the distal aorta using transcatheter techniques with good outcomes on mid-term to long-term follow-up. 5,7,11) Meanwhile, migration of prostheses into the LV can be more challenging, and in such cases, immediate conversion to surgical treatment is often required. 5,10) To the best of our knowledge, only 4 cases have been reported which could be recovered using a transcatheter approach without conversion to surgery: two cases were resolved using the transapical approach, 12,13) and the others using the transfemoral approach.…”
Section: Discussionmentioning
confidence: 99%
“…8,2 Treatment of embolization into the aorta has traditionally relied on repositioning the valve into the descending aorta using endovascular snares or removal via open surgery. 8,9 Other strategies have included repositioning the valve using a valvuloplasty balloon or deploying a large stent inside the embolized valve to hold the leaflets in the open position. 10 Patients with prosthesis embolization have a high risk of mortality 11 and morbidity including stroke, 7 occlusion of major arteries, 7 and aortic dissection 12 associated with manipulation of the prosthesis in the ascending aorta.…”
Section: Transcatheter Aortic Valve Replacement #2 and Capturementioning
confidence: 99%